Sistem elektronik penasihat akademik bagi pelaporan dan pemantauan sistem penasihat akademik universiti teknologi MARA (UiTM) (Academic advisory electronic system for reporting and monitoring of universiti teknologi MARA (UiTM) academic advisory system) / Kardina Kamaruddin …[et al.] - Kamaruddin, Kardina; Ishak, Hadzli; Ahmad, Abdul Majeed; Hussain, Siti Hajar; Azman, Azlin; Mohammad Yunus, Fauziah; Shawalludin, Syahrini; Omar, Hapiza; Abdul Rahman, Syahrul Nadwani (Universiti Teknologi MARA, 2020)
The e-PA system was developed to establish a monitoring and reporting process for academic adviser (PA) and student (advisee) to be used in the UiTM Kedah Academic Affairs Division (BHEA). The ePA system is an online system that enhances the process of monitoring and reporting of PA-advisee activities. The e-PA system utilized the Design Thinking approach which is an approach in empowering innovation that was identified to value functionality. Therefore, the e-PA system are 65 categorized in 3 phases which were: Hear (H) which was Emphatize-activity aiming to visualize and analyze users’ needs; Create (C) - this phase encompassed Define-and-Ideate-activities aiming to find inventions that meets the value of functionality; and Deliver (D) which covers the Prototype-and-Testactivities where the e-PA system was developed through the provision of prototypes and had been through 3 trials and finally tested with four target groups. The results of the e-PA system development had achieved significant reductions in terms of cost and time. In addition, the objectives of 25 percent innovation creation indication had also been achieved through the aspects of organizational function, customer needs, stakeholders, and current conditions and ecosystems of the campus. The e-PA system could be a platform of communication to facilitate monitoring and reporting of PA-advisee activities for all stakeholders at UiTM Kedah Branch. The e-PA system can enhance PA's roles by helping BHEA to empower PA-advisee relationships, increase customer satisfaction, maximize students’ success in accordance with the aspirations of the Higher Education Ministry, and assist the campus to achieve a "green-university" status. This three-phase-interaction system is a precedent system in the monitoring and reporting of PA-advisors at UiTM Kedah Branch.